2019
DOI: 10.1111/radm.12362
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial co‐creation: societal impact through open innovation

Abstract: New open innovation initiatives, such as accelerators, living labs, social innovation labs andopen labs, involve for-profit and not-for-profit actors working closely together to co-create both business value and societal impacts. However, there is a lack of theoretical underpinning to understand how and why co-creation by actors generate different types of social value in the concurrent pursuit of business and social value. Adopting an inductive case study approach, we find that different types of entrepreneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
37

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 62 publications
2
64
0
37
Order By: Relevance
“…Investing in generic social issues with no dynamic effects and which are neither significantly influenced by the enterprise's operations nor affect its long-term competitiveness is a waste of corporate wealth. De Silva and Wright [39] indicated that strategic philanthropy is most often associated with open innovation. Accordingly, profit companies are likely to collaborate and co-create value with non-profit organizations through open innovation approaches.…”
Section: The Charitable Csrmentioning
confidence: 99%
“…Investing in generic social issues with no dynamic effects and which are neither significantly influenced by the enterprise's operations nor affect its long-term competitiveness is a waste of corporate wealth. De Silva and Wright [39] indicated that strategic philanthropy is most often associated with open innovation. Accordingly, profit companies are likely to collaborate and co-create value with non-profit organizations through open innovation approaches.…”
Section: The Charitable Csrmentioning
confidence: 99%
“…The literature has clearly highlighted the difficulties associated with the simultaneous achievement of social and business goals, since actors have to bridge potentially conflicting aims and divergent stakeholder interests (Pache and Santos 2013;Ebrahim et al 2014). Yet, at the individual level, close and tight interactions could address this challenge (De Silva et al 2019). These individuals might be from different organisations, including those with both for-profit and not-forprofit motives.…”
Section: Agents' Interactions In Science-based Co-creationmentioning
confidence: 99%
“…The involvement of multiple partners who co-create shared value may give rise to intellectual property (IP) issues. Whether a clear IP strategy for co-creation would be critical depends upon the stage of co-creation, the types of actors involved in the initiative and the type of objectives (De Silva and Wright 2019). Arranging IP agreements in advance, however, is a sensitive issue, and should thus be devoted careful consideration.…”
Section: (C) Managing Co-creationmentioning
confidence: 99%
“…O primeiro elemento, engajamento dos stakeholders, se mostrou importante nos estudos de casos investigados por demonstrar a relevância de atores internos e externos próximos à organização no processo de criação de valor social (Silva & Wright, 2019). Evidências sugerem que quanto maior a aproximação desses atores, seja para formação de redes, cluters, parcerias, contatos, colaborações, alianças e cooperações, maior é a possibilidade de alcançar seus objetivos sociais (Collazzo-Yelpo & Kubelka, 2019;Kolk & Lenfant, 2015).…”
Section: Valor Socialunclassified